Pressotherapy of a postoperative scar with the application of non-sterile silicone dressings in a 56-year-old woman treated for breast cancer in the Holycross Cancer Centre in Kielce - Macek, Paweł; Terek-Derszniak, Małgorzata; Lipińska, Anna; Błaszkiewicz, Ewa; Król, Halina; Głuszek, Stanisław; Góźdź, Stanisław (Medical Studies/Studia Medyczne, 2015)
Scarring is a natural process of wound healing. In some cases, however, there is formation of hypertrophic scars and keloids that are the result of collagen decomposition and synthesis. A disturbed scarring process causes functional, aesthetic, and psychological disorders in the patient. Silicone dressings in the form of plasters or gel are used in the treatment of hypertrophic scars and keloids. A case of pressotherapy of a postoperative scar with the use of non-sterile silicone dressings in a 56-year-old patient treated for breast cancer is described herein. The use of a 2-month pressotherapy of the scar resulted in an improvement in all the assessed parameters. Pressotherapy of the postoperative scar in the patient after mastectomy proved to be an effective and promising method. However, the methods of the scar assessment before and after treatment need objectivity.